الخطّ العربي وتجليّاته في الحضارة الإسلامية – المساجد أنموذجا - شروق دحماني; الدكتورة: بختة تاحي (Universitas Negeri Malang, 2022)
Arabic calligraphy is the supreme and sophisticated pillar that distinguishes Islamic arts, as we note that not an Islamic artwork is devoid of mosques, palaces, buildings, and walls, except that we found in it authentic Islamic inscriptions represented in the ancient Arabic calligraphy, which is wonderful in its decoration and refined in its expressions, and is distinguished in its drawings. The embroidered craftsmanship and mastery astonish the beholder. Where the interest in the latter has become a treasure and a beacon for calligraphers, their love for it tends to be associated with the tolerant and pure Islamic religion in its teachings, which led them to interact with various civilizations and to spread and display its distinctive images and forms, as well as to the diversity and different methods of Arabic calligraphy and the multiplicity of its models and its promotion to the highest ranks among the arts. From here we pose the forms: What is meant by the Arabic calligraphy? What are the main types of Arabic fonts? What are its manifestations and developments?